Methods of Assessment and Evaluation in Medical Science Education - Vageriya V. (Medicine and Medical Research: New Perspectives Vol. 8, 2024)
The assessment and evaluation is an essential and important aspect of medical science education. It encourages and motivates students to learn in a better way. A good assessment is key to lifelong learning. Education is the backbone of a nation. During the last two decades, medical education faced a lot of challenges. These challenges are raised by patients, their relatives, healthcare workers and society. After a thorough discussion with experts, solutions come out in the form of the development of a new curriculum, the introduction of new learning methods, and introduction of the new methods of evaluation and assessment. Many innovative methods of teaching, learning, assessment and evaluation are included in medical science. Medical education is based on learner skills and practice. Without practice, a person cannot work in this field. The aim of this paper is to describe the various assessment methods in medical education. There is a huge difference between traditional and modern education. Students of the 21st century are technology-based so teachers must be equipped with technology. Nowadays the word teaching is replaced by term learning. Students having already the entire subject-related material on their computer or mobile. The work of the teacher is to explain the concept. During assessment of teaching, 2 methods are very familiar, which are formative and summative assessment. Formative assessment is carried out by a teacher to find the knowledge of a learner at the end of each chapter or unit. The teacher can also evaluate his classroom or teaching performance after each lecture. A summative assessment is carried out at the end of the semester or year to evaluate the overall performance of a candidate. It is also known as term examination or cumulative examination. Nowadays, many new methods are available for teaching in medical education like demonstration and simulation. Every teacher must be thorough with methods of assessment and evaluation. Conclusion: It can be concluded from the literature that planning for effective faculty development programs is required. These programs are to be tailored to teachers’ needs about their ability to guide students’ learning. Clinical simulation, online webinars, panel discussions, symposiums and objective structured clinical examination (OSCE) are new methods used for assessment of students.